ANALISIS HAMBATAN GURU DALAM MENGIMPLEMENTASIKAN KURIKULUM MERDEKA PADA MATA PELAJARAN IPAS SD NEGERI 11 KOTA BANDA ACEH - Magfirah, Siti; Aswita, Dian; Maulidar, Maulidar (Jurnal Seramoe Education, 2025)
This research aims to determine teachers' obstacles in implementing the independent curriculum in science and science subjects at SD Negeri 11 Banda Aceh. The approach in this research is a qualitative approach with descriptive research type. The subjects in this research used a total sampling technique, meaning that all 35 class V students and 1 class V teacher were the research subjects. The collection techniques in this research are interviews and observations. Data analysis techniques in this research include data reduction, data presentation and drawing conclusions. The results of this research were obtained from teacher interviews, teacher observations, and student observations. In the results of this research there are differences in interviews and observations, the results of the interviews do not match the results of the observations made, in this case there are still obstacles in implementing the independent curriculum in science and science subjects. Where teachers still have difficulty in determining appropriate learning methods and strategies for students so that the learning process becomes enjoyable in the learning process. Thus, the final conclusion is that there are still obstacles for teachers in implementing the independent curriculum in science and science subjects at SD Negeri 11 Banda Aceh City.